Genomic characterization of parvovirus and beak and feather disease virus in cockatiel (Nymphicus hollandicus) - Subir Sarker; Saranika Talukder; Md. Safiul Alam Bhuiyan; Md. Hakimul Haque (American Society for Microbiology, 2024)
This study reveals the genomes of psittaciform chaphamaparvovirus 5 (PsChPV-5) and a beak and feather disease virus (BFDV), discovered in the fecal samples of cockatiels. The genomes of PsChPV-5 and BFDV are 4,366 and 2,009 base pairs long, respectively, each exhibiting the characteristic genomic structures of their respective genera.